2022
DOI: 10.4236/ojmm.2022.123010
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Blood Isolates in Children: Conventional vs. Bactec Automated Blood Culture System in a Tertiary Health Centre in Gombe, North East Nigeria

Abstract: Background/Aim: Blood culture is critical in the diagnosis and treatment of blood stream infections (BSIs) especially in children. BSIs are among the most common cause of morbidity/mortality and blood culture has remained the gold standard for diagnosis. We sought to compare Blood Culture Isolates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Studies [19] [20] [21] from developing countries showed that automated systems show better performance than manual systems in terms of yield, sensitivity and especially speed of growth and overall turnaround time. We had earlier reported higher pathogen yield with Bactec compared to manual culture method in children in our facility [22].…”
Section: Introductionmentioning
confidence: 69%
“…Studies [19] [20] [21] from developing countries showed that automated systems show better performance than manual systems in terms of yield, sensitivity and especially speed of growth and overall turnaround time. We had earlier reported higher pathogen yield with Bactec compared to manual culture method in children in our facility [22].…”
Section: Introductionmentioning
confidence: 69%
“…Blood culture positivity trend was higher and sustained in the Bactec era compared to the Manual era. Previous reports in Nigeria [11] [37] [38] [39] and elsewhere [12] [13] [40] have shown higher pathogen yield and shorter turnaround time with Bactec culture systems over the conventional/manual method. However, and in general, access to quality-assured laboratory diagnosis has been a challenge in low-income and middle-income countries (LMICs) resulting in delayed or inaccurate diagnosis and ineffective treatment with consequences for patient safety [41] [42].…”
Section: Discussionmentioning
confidence: 99%
“…In these settings, the conventional/ manual culture methods remain the dominant systems while the automated blood culture systems have become the standard in high-income countries (HICs), and are relatively expensive and not universally available for implementation in most LMICs where [7] [8] [9] implementing automated microbiologic systems is feasible [7] [10]. Several reports [11] [12] [13] in LMIC showed that these systems show better performance than manual systems in terms of yield, sensitivity and especially speed of growth and overall turnaround time. Blood cultures are still indispensable for the diagnosis of BSIs however currently available molecular methods based on in situ hybridization-based methods, DNA microarray-based hybridization technology; nucleic acid amplification-based methods and combined methods [14] are a distant prospect for LMICs.…”
Section: Introductionmentioning
confidence: 99%